Uniform dispersion of silica nanoparticles on dyed cellulose surface by sol–gel method - Hou, Aiqin; Yu, Yanhong; Chen, Huawei (Carbohydrate polymers, 2010)
Cellulose fabric is dyed with Reactive Red B-3BF. Dispersion of silica nanoparticles on dyed cellulose surface is investigated. Novel color cellulose/silica surface is prepared and characterized by FT-IR, AFM and FSEM. The color data of the cellulose/silica surface are discussed by reflectance spectra, color yield ( K/ S). The results show that silica nanoparticles form smooth film with high degree of homogeneity on the cellulose surface. The surface color shade of the dyed cellulose can be affected by sol–gel. The K/ S of two sample surfaces have noticeable increase. With increasing silica nanoparticles, the K/ S of samples have further improvement. The thin film imparts low reflectance index and increases color yield.